Volume 1: Aircraft Engine; Ceramics; Coal, Biomass and Alternative Fuels; Controls, Diagnostics and Instrumentation; Education; 2009
DOI: 10.1115/gt2009-59166
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of Some Novel Concepts for High Bypass Ratio Turbofan Engines

Abstract: The soaring fuel price and the burgeoning environmental concerns have compelled global research towards cleaner engines, aimed at substantial reduction in emission, noise and fuel consumption. In this context, the present research investigates the feasibility of some novel engine concepts, namely Geared Turbofan and Intercooled Recuperated Turbofan concepts, by hypothetically applying them into an existing state-of-the-art high bypass ratio engine. This paper made an effort to estimate the effects on the basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This work mainly focuses on the theoretically obtainable performance of the isolated propulsion unit, especially in terms of thrust specific fuel consumption (TSFC), but also presents a preliminary analysis of installation effects, in terms of penalties related to the increased size of the nacelle. As the BPR increases, technological developments are introduced to improve the performance of the turbofan, such as the geared solution for the fan [61,62], the variable pitch mechanism for its blades (variable pitch fan, VPF, [63]) and the variable area nozzle (VAN, [64]). In particular, the VPF, as well as providing optimal operating matching of the fan under all working conditions, enables the fan to be allocated the function of a thrust reverser, eliminating the need to integrate it into the nacelle and thus permitting a much more compact design of the latter.…”
Section: Uninstalled Uhbr Turbofan Featuresmentioning
confidence: 99%
“…This work mainly focuses on the theoretically obtainable performance of the isolated propulsion unit, especially in terms of thrust specific fuel consumption (TSFC), but also presents a preliminary analysis of installation effects, in terms of penalties related to the increased size of the nacelle. As the BPR increases, technological developments are introduced to improve the performance of the turbofan, such as the geared solution for the fan [61,62], the variable pitch mechanism for its blades (variable pitch fan, VPF, [63]) and the variable area nozzle (VAN, [64]). In particular, the VPF, as well as providing optimal operating matching of the fan under all working conditions, enables the fan to be allocated the function of a thrust reverser, eliminating the need to integrate it into the nacelle and thus permitting a much more compact design of the latter.…”
Section: Uninstalled Uhbr Turbofan Featuresmentioning
confidence: 99%
“…Additionally, according to Dewanji [5], decreased LP spool speed could not satisfy the torque to drive the sizeable rotating fan. Thus, the LP spool is likely to be bulkier for torque relief, creating a larger core dimension.…”
Section: Introductionmentioning
confidence: 99%
“…The GTF would improve SFC and save 2.2% and 3.0% of the fuel consumption by increasing the BPR from 12.5 to 13.5 [4]. Dewanji [5] studied several GTF cases and revealed that the GTF with high BPR was effective in engine weight and SFC reduction. Alexiou [7] presented an ultra-high bypass ratio (UHBPR) GTF engine model with variable pitch fan (VPF), which showed good potential as candidate architecture at high BPR levels.…”
Section: Introductionmentioning
confidence: 99%